2004
DOI: 10.1007/s00424-004-1316-z
|View full text |Cite
|
Sign up to set email alerts
|

Cell-volume-dependent vascular smooth muscle contraction: role of Na+, K+, 2Cl? cotransport, intracellular Cl? and L-type Ca2+ channels

Abstract: This study elucidates the role of cell volume in contractions of endothelium-denuded vascular smooth muscle rings (VSMR) from the rat aorta. We observed that hyposmotic swelling as well as hyper- and isosmotic shrinkage led to VSMR contractions. Swelling-induced contractions were accompanied by activation of Ca2+ influx and were abolished by nifedipine and verapamil. In contrast, contractions of shrunken cells were insensitive to the presence of L-type channel inhibitors and occurred in the absence of Ca2+ o. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
35
1
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 58 publications
(79 reference statements)
7
35
1
6
Order By: Relevance
“…The relaxing mechanism of swelling may be explained in the following two ways: 1) effects on intracellular Ca 2+ movement and 2) an inhibition of contractile elements. It has been suggested that Cl -movement is related to the [Ca 2+ ]i level in canine basilar arteries [26] and the rat aorta [1] and trachea [4]. However, in our study, I-154 K + solution induced a sustained increase of [Ca 2+ ]i level in the bovine trachea.…”
Section: Discussioncontrasting
confidence: 86%
“…The relaxing mechanism of swelling may be explained in the following two ways: 1) effects on intracellular Ca 2+ movement and 2) an inhibition of contractile elements. It has been suggested that Cl -movement is related to the [Ca 2+ ]i level in canine basilar arteries [26] and the rat aorta [1] and trachea [4]. However, in our study, I-154 K + solution induced a sustained increase of [Ca 2+ ]i level in the bovine trachea.…”
Section: Discussioncontrasting
confidence: 86%
“…Effect of bumetanide with data obtained in a study on contractions of depolarized endothelium-denuded strips from rat aortae [22]. We did not observe any inhibitory action of bumetanide on contractions triggered by ATP, whereas contractions of UTP-treated arteries were decreased by 60% (Fig.…”
Section: Effect Of P2 Antagonistssupporting
confidence: 56%
“…Ca 2+ release from the endoplasmic reticulum elicits activation of Cl − channels, plasma membrane depolarization and activation of long-lasting L-type Ca 2+ channels, whose involvement in MT is well-documented in an overwhelming number of vessels studied so far [3]. Significantly, NKCC inhibition partially blocked the depolarizing action of Cl − channel activation via attenuation of [Cl -] i , as demonstrated in bumetanide-and furosemidetreated smooth muscle cells of different origins [20][21][22], and resulted in the MT suppression documented here (Fig. 6).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations